Biomonitoring for traditional herbal medicinal products using DNA metabarcoding and single molecule, real-time sequencing - Tianyi Xin; Zhichao Xu; Jing Jia; Christine Leon; Songnian Hu; Yulin Lin; Subramanyam Ragupathy; Jingyuan Song; Steven G. Newmaster (Elsevier, 2018)
Global concerns have been paid to the potential hazard of traditional herbal medicinal products (THMPs). Substandard and counterfeit THMPs, including traditional Chinese patent medicine, health foods, dietary supplements, etc. are potential threats to public health. Recent marketplace studies using DNA barcoding have determined that the current quality control methods are not sufficient for ensuring the presence of authentic herbal ingredients and detection of contaminants/adulterants. An efficient biomonitoring method for THMPs is of great needed. Herein, metabarcoding and single-molecule, real-time (SMRT) sequencing were used to detect the multiple ingredients in Jiuwei Qianghuo Wan (JWQHW), a classical herbal prescription widely used in China for the last 800 years. Reference experimental mixtures and commercial JWQHW products from the marketplace were used to confirm the method. Successful SMRT sequencing results recovered 5416 and 4342 circular-consensus sequencing (CCS) reads belonging to the ITS2 and psbA-trnH regions. The results suggest that with the combination of metabarcoding and SMRT sequencing, it is repeatable, reliable, and sensitive enough to detect species in the THMPs, and the error in SMRT sequencing did not affect the ability to identify multiple prescribed species and several adulterants/contaminants. It has the potential for becoming a valuable tool for the biomonitoring of multi-ingredient THMPs. KEY WORDS: Traditional herbal medicinal products (THMP), Species mixture, Authentication, DNA metabarcoding, Single molecule real-time (SMRT) sequencing, Circular-consensus sequencing (CCS)